Penerapan Metode Fault Tree Analysis Untuk Mencegah Kegagalan Pada Departemen Interior di PT X - Yolanda, Metta; Ekawati, Yurida; Noya, Sunday (Teknik Industri Universitas Ma Chung, 2023)
The Interior Department is one of the departments of PT X that produces bus and minibus interior parts. During the interior production process there are still quite a lot of defective products. There are six types of defects, namely air bubbles, not 100% printed, double tip insulation does not stick, torn, too dense/less dense, and color striped. The main focus of this research is to analyze the causes of failure of a process and make recommendations for improvements that can be made using the Fault Tree Analysis (FTA) method. From the FTA, improvements are needed to reduce defects in the Interior Department. Recommendations for improvement that can be given to the company are to create a checklist form to make it easier for operators to clean the mattress regularly, to check that the non-stick liquid has been sprayed twice, to ensure that the mattress has been heated every morning, to ensure that the paint has been shaken before use so that there are no striped colors, and to ensure that the paint has been sprayed twice. Then the next improvement recommendations are to provide and attach a standard description to each injection number on each product, make a machine maintenance schedule, replace the non-stick liquid with an old model that is not too strong, provide a timer on the mattress that is used as a reminder when waiting for the paint to dry, procure a mattress equipped with a sound sensor, and procure a generator.